Seasonal variation of energy expenditure in Japanese macaques (Macaca fuscata). (August 2018) - Sha, John Chih Mun; Kurihara, Yosuke; Tsuji, Yamato; Take, Makiko; He, Tianmeng; Kaneko, Akihisa; Suda-Hashimoto, Naoko; Morimoto, Mayumi; Natsume, Takayoshi; Zahariev, Alexandre; Blanc, Stéphane; Hanya, Goro
Abstract: Animals living in seasonal environments must adapt to a wide variation of temperature changes which requires flexible adjustments of time budget and metabolic processes for efficient thermoregulation. The Japanese macaque ( Macaca fuscata ) is one of only a handful of nonhuman primate species that experience seasonal climates over a wide temperature range. We used behavior observations, accelerometer sensors and the doubly-labelled water (DLW) method to measure activity and total daily energy expenditure (TDEE) of M. fuscata housed in captivity but exposed to natural seasonal variations at day lengths ranging from 10 to 12 h and temperature ranging from 0° to 32°C. Although overall activity was significantly lower in winter compared to summer and autumn, we found no effect of temperature on day-time activity. However nocturnal inactivity and mean length of sleeping bouts significantly increased along a gradient of decreasing temperatures from summer through winter, suggesting the importance of adaptive behavioral thermoregulation in this species. Energy expenditure that was unaccounted for by Basal Metabolic Rate (BMR) and physical activity i.e. expended through diet-induced thermogenesis or thermoregulation was between 14% and 32%. This residual energy expenditure differed between summer/autumn and winter and was relatively consistent across individuals (approximately 5–8% higher in winter). The percentage of body fat and residual energy expenditure were negatively correlated, supporting that fat storage was higher when less energy was required for thermoregulation. Our results suggest that physiological mechanisms like behavioral and autonomic thermoregulation enable M. fuscata to adapt to wide fluctuations in environmental conditions which provide insights into the evolutionary adaptations of nonhuman primates in seasonal climate. Highlights: The Japanese macaque is one of only a handful of primate species that experience seasonal climates. We studied activity and energy expenditure over 3 seasons in temperatures ranging from 0° to 32°C. We found low variability in seasonal energy expenditure, approximately 5–8% higher in winter. Temperature influenced nocturnal inactivity and sleep bout length but not diurnal activity. Behavioral and metabolic adaptations are important for regulating energy expenditure.